2021
DOI: 10.18488/journal.1.2021.112.129.136
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Reading Difficulty Using Socio-Affective Strategy

Abstract: Reading academic texts requires learners to use a variety of skills and strategies. Among the main types of academic reading are (a) reading for quick reference, (b) reading for pleasure and also (c) critical reading. Students who have just left high schools, reading academic text may post some problems. Hence, readers face challenges when they read academic texts. Different readers face different difficulties when they read different types of texts. Some readers face linguistics challenges while some face non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…In terms of socio-affective strategies, the finding of the study conducted by Rahman et al (2021), who investigated 159 Malaysian respondents as the subject of their research by using a descriptive quantitative research design, revealed it could not be denied that students, during reading activities, did experience few difficulties both in term of linguistics (i.e., vocabulary & syntactic knowledge) and non-linguistics (i.e., attitudes, motivation & background knowledge).…”
Section: Previous Studiesmentioning
confidence: 99%
“…In terms of socio-affective strategies, the finding of the study conducted by Rahman et al (2021), who investigated 159 Malaysian respondents as the subject of their research by using a descriptive quantitative research design, revealed it could not be denied that students, during reading activities, did experience few difficulties both in term of linguistics (i.e., vocabulary & syntactic knowledge) and non-linguistics (i.e., attitudes, motivation & background knowledge).…”
Section: Previous Studiesmentioning
confidence: 99%